1991
DOI: 10.1073/pnas.88.23.10821
|View full text |Cite
|
Sign up to set email alerts
|

An extraovarian protein accumulated in mosquito oocytes is a carboxypeptidase activated in embryos.

Abstract: We report a phenomenon previously unknown for oviparous animals; in Aedes aegypti mosquitoes a serine carboxypeptidase is synthesized extraovarially and then internalized by oocytes. The cDNA encoding mosquito vitellogenic carboxypeptidase (VCP) was cloned and sequenced. The VCP cDNA hybridizes to a 1.5-kilobase mRNA present only in the fat body of vitellogenic females. The deduced amino acid sequence of VCP shares significant homology with members of the serine carboxypeptidase family. Binding assays using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 32 publications
2
57
0
4
Order By: Relevance
“…Its synthesis in the female fat body is initiated by blood feeding, and the kinetics of its secretion by the vitellogenic fat body are similar to those of the yolk protein precursors, Vg (59) and VCP (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its synthesis in the female fat body is initiated by blood feeding, and the kinetics of its secretion by the vitellogenic fat body are similar to those of the yolk protein precursors, Vg (59) and VCP (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known, however, about the process of yolk protein degradation in the mosquito embryo. Previously, we have found that during vitellogenesis, the female fat body, a metabolic tissue analogous to the vertebrate liver, synthesizes and secretes a latent proenzyme of a serine carboxypeptidase which is homologous to yeast carboxypeptidase Y (42,43). This 53-kDa proenzyme, which we named vitellogenic carboxypeptidase (VCP), 1 is specifically accumulated by developing oocytes and deposited in yolk bodies.…”
mentioning
confidence: 99%
“…Activation of these enzymes is achieved by luminal acidification of YGs, a process that is mediated by proton pumps (Fagotto, 1991;Nordin et al, 1991;Mallya et al, 1992;Fagotto, 1995). VT and hydrolases, such as cathepsin B and carboxypeptidase, are known to accumulate in the oocytes during oogenesis and to be stored in YGs (Wall and Meleka, 1985;Oliveira et al, 1986;Raikhel and Dadhialla, 1992;Valle, 1993;Sappington and Raikhel, 1998;Cho et al, 1991;Cho et al, 1999;Liu and Nordin, 1998;Yin et al, 2001). Newly laid eggs are therefore able to initiate VT degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The exact origin of these hydrolases is poorly understood but some of these enzymes are also taken into the oocytes during oogenesis, being stored near yolk proteins in an inactive state. Aedes aegypti carboxypeptidase (Cho et al, 1991) and cathepsin B-like protease (Cho et al, 1999), Blatella germanica vitellin-processing protease and Xenopus laevis lysosomal enzymes have been shown to accumulate in the oocytes during oogenesis (Wall and Meleka, 1985;Liu and Nordin, 1998;Yin et al, 2001). To activate hydrolases, YGs undergo a process of acidification mediated by proton pumps, such as proton ATPases (H + LYGs.…”
Section: Introductionmentioning
confidence: 99%
“…In the anautogenous mosquito Aedes aegypti, a key model vector, the fat body produces several YPPs: vitellogenin, vitellogenic carboxypeptidase, and vitellogenic cathepsin B (5,6,8).…”
mentioning
confidence: 99%